2014
DOI: 10.1111/poms.12203
|View full text |Cite
|
Sign up to set email alerts
|

The Strategic Role of Third‐Party Marketplaces in Retailing

Abstract: R etailers are increasingly adopting a dual-format model. In addition to acting as traditional merchants (buying and reselling goods), these retailers provide a platform for third-party (3P) sellers to access and compete for the same customers. We investigate the strategic rationale for a retailer to introduce a 3P marketplace. Our analysis provides insights into the growing prevalence of 3P marketplaces. We show that by committing to having an active 3P marketplace, the retailer creates an "outside option" th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(111 citation statements)
references
References 27 publications
(33 reference statements)
0
108
3
Order By: Relevance
“…However, 3PL's compete for the same customers and are forced to serve multiple customers at the same time (Mantin et al 2014;Shi et al 2016). In contrast to basic commodity like logistics service provision, is that of a solution or systems integrator role, typically called fourth-party logistics (4PL) providers (Win 2008;Huemer 2012).…”
Section: Logistics Service Provision and Competitive Marketsmentioning
confidence: 99%
“…However, 3PL's compete for the same customers and are forced to serve multiple customers at the same time (Mantin et al 2014;Shi et al 2016). In contrast to basic commodity like logistics service provision, is that of a solution or systems integrator role, typically called fourth-party logistics (4PL) providers (Win 2008;Huemer 2012).…”
Section: Logistics Service Provision and Competitive Marketsmentioning
confidence: 99%
“…Abhishek et al [3] provided that the mode choice of the platform enterprise between agency selling and reselling was relevant to the effect of sales in the electronic channel on the demand in the traditional channel. Mantin et al [24] found out that e-tailer's power of bargaining with the manufacturer could be increased after he built the platform and it benefited the consumers, but it would decrease the consumers' benefits if the power is too big. Jiang et al [25] used "Mid Tail" theory to analyze the mode selection problem of the platform e-tailer and suggested that the e-tailer might select different modes for different kinds of products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is worth noting that a third-party seller can be any reseller who distributes products or a manufacturer who directly sells products. Martin et al refer to this business mode as "dual format" retailing (DF) [4]. A critical distinction between the reselling and agency selling formats is who sets the retail price.…”
Section: Introductionmentioning
confidence: 99%